АНАЛИЗ ИНТЕНСИВНОСТИ ДЕФОРМАЦИЙ РУСЛА В РАЗНЫЕ ФАЗЫ ВОДНОГО РЕЖИМА (НА ПРИМЕРЕ УЧАСТКА СРЕДНЕЙ ОБИ) - Каргаполова И.Н.; Сурков В.В. (My University, 2003)
Channel deformation rate at different phases of water regime was analysed. Conditions of sediment accumulation and breaking-up were determined and mobility of sediment was evaluated. The phase of maximum channel deformation intensity corresponds to the moments of channel-forming discharge.
Keywords: 551.435.13(282.251.1)